Persepsi Mahasiswa Surabaya Terhadap Pemberitaan Isu Penolakan Timnas Israel Dalam Piala Dunia U-20 - Liza Shafira Ningtyas; Catur Suratnoaji (Jurnal Ilmiah Wahana Pendidikan, 2023)
Indonesia was reported to have been appointed to host the U-20 world cup in 2021, but had to be postponed due to unfavorable conditions at that time due to the Covid-19 pandemic. After long processes, Indonesia was still appointed by FIFA to host the U-20 World Cup. Of all the 24 countries that will compete, Israel is also a member of it. The news was certainly welcomed by the Indonesian people. However, on the other hand there are a numbers of people who are against it. Several politicians reportedly rejected the Israeli national team which resulted in the cancellation of Indonesia being the host. This issue then received the attention of all Indonesian people, including college students. This study discusses the perceptions of college students in Surabaya towards news on the issue of rejection of the Israeli National Team in the U-20 World Cup using descriptive qualitative methods and data collection techniques by in-person and online interviews. Based on the results of using 6 college student informants, 3 out of 6 active informants criticized politicians who refused through their social media. News on the issue of rejection is impacting on college students perceptions and can influence them to take action